الفواعل غير الدولية: مقاربة في المسببات والأدوار - رحمين, نهاد; كواشي, عتيقة (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2021)
تركز هذه الدراسة على مسألة في غاية الأهمية ناتجة عن إفرازات النظام العالمي هي الفواعل غير الدولية التي نقوم بالبحث فيها لإبراز محفزات ومسببات ظهور هذه الفواعل في الساحة الدولية والتدقيق في المفهوم ثم فحص أدواره خلال التفاعل الدولي، عبر دراسة الاشكالية: ماهي الأسس المعرفية للفواعل غير الدولية وكيف تؤثر في العلاقات الدولية؟ والقائمة على فرضية أن انخراط الفواعل غير الدولية في التفاعلات الدولية يزيد من تأثيرها ويعزز دورها في النظام العالمي. من خلال الدراسة توصلنا إلى أن العولمة الاقتصادية وسيطرة الأسواق، الثورة المعلوماتية والتكنولوجية وتزايد مستويات التفاعل الدولي، فضلا عن التغيير في بنية النظام الدولي من مسببات ظهور الفواعل غير الدولية، أما تحليل الأدوار والتأثير أظهرت لنا امتلاك هذه الفواعل لسلطة وفعالية تمكنها من ممارسة الضبط على كل المستويات. abstract: Abstract: This study focuses on the very important issue resulting from the secretions of the world order, namely, the non-state actors that we are researching to highlight causes of the emergence of these factors , to scrutinize the concept and then to examine its roles during international interaction, through the study of the problem: what are the knowledge bases of non-state actors and how do they affect international relations? It is based on the premise that the involvement of non-international groups in international interactions increases their impact and enhances their role in the global system. Through the study we found that economic globalization and market control, the information and technological revolution , as well as the change in the structure of the international system are the causes of the emergence of non-international factors, but the analysis of roles and influence has shown us that these factors have an authority and effectiveness that enables them to exercise control at all levels.